Political violence in russia of putin. what happened to political opponents of vladimir putin? (2009)
Since Vladimir Putin came to power in 2000, has formed a petrostate, based on the wealth of oil, while strengthening a new bureaucracy and a new industrial economy. The Russian managed democracy, as has been cataloged, it’s just a hint of a political system that hides a dictatorshi p, as the monopoly of political power is held by a single party, United Russia, leaving truce to political parties dissident forces with the design that prevent the release of the opposition to submit their proposals. The growing public protests against the policies of the government through violent attack leaving the full totalitarian policies of the twentieth century no longer remember the freedoms and the rule of law, democracy is threatened.In the following essay we analyze the role played by political dissent by the Russian President Vladimir Putin on his two presidential governments (2000-2004 and 2004-2008) and how we view the politics taken by the regime of Vladimir Putin to silence these voices.